Phantom limb therapy improves cortical efficiency of the sensorimotor network in a targeted muscle reinnervation amputee: a case report - Borrell, Jordan A.; Manattu, Arun Karumattu; Copeland, Christopher; Fraser, Kaitlin; D’Ovidio, Andrew; Granatowicz, Zach; Lesiak, Alex C.; Figy, Sean C.; Zuniga, Jorge M. (Frontiers in Neuroscience, 2023)
Targeted muscle reinnervation (TMR) surgery involves the coaptation of amputated nerves to nearby motor nerve branches with the purpose of reclosing the neuromuscular loop in order to reduce phantom limb pain. The purpose of this case study was to create a phantom limb therapy protocol for an amputee after undergoing TMR surgery, where the four main nerves of his right arm were reinnervated into the chest muscles. The goal of this phantom limb therapy was to further strengthen these newly formed neuromuscular closed loops. The case participant (male, 21 years of age, height = 5’8” and weight = 134 lbs) presented 1 year after a trans-humeral amputation of the right arm along with TMR surgery and participated in phantom limb therapy for 3 months. Data collections for the subject occurred every 2 weeks for 3 months. During the data collections, the subject performed various movements of the phantom and intact limb specific to each reinnervated nerve and a gross manual dexterity task (Box and Block Test) while measuring brain activity and recording qualitative feedback from the subject. The results demonstrated that phantom limb therapy produced significant changes of cortical activity, reduced fatigue, fluctuation in phantom pain, improved limb synchronization, increased sensory sensation, and decreased correlation strength between intra-hemispheric and inter-hemispheric channels. These results suggest an overall improved cortical efficiency of the sensorimotor network. These results add to the growing knowledge of cortical reorganization after TMR surgery, which is becoming more common to aid in the recovery after amputation. More importantly, the results of this study suggest that the phantom limb therapy may have accelerated the decoupling process, which provides direct clinical benefits to the patient such as reduced fatigue and improved limb synchronization.